INOVASI PEDAGOGIS BERBASIS MAZHAB FIQIH: REFORMULASI PEMBELAJARAN PENDIDIKAN AGAMA ISLAM YANG RESPONSIF TERHADAP KESETARAAN GENDER - Izzatul Mahya; Hanna Nessa Anantasya; Alfiah Nur Futikha; Malihatul Afifah; Siyono (Jurnal Ilmu Pendidikan Islam, 2025)
Gender-responsive education is an educational approach that encourages the active involvement of all students regardless of gender, so that there are no boundaries between male and female roles. The main objective of gender-responsive education is to achieve gender equality through a learning process that provides students with an understanding of how to position the roles of women and men in a balanced and fair manner in life. In the context of Islamic education, gender issues need to be internalized through several approaches, one of which is the approach of the four schools of fiqh. This study uses a qualitative approach with a library research method to examine in depth the concept of gender in Islamic education based on the schools of fiqh. The results of the study produced a gender-based Islamic education learning design through a comparison of the four schools of fiqh. Pendidikan responsif gender adalah pendekatan pendidikan yang mendorong keterlibatan aktif semua peserta didik tanpa membedakan jenis kelamin, sehingga tidak ada batasan antara peran laki-laki dan perempuan. Tujuan utama pendidikan responsif gender adalah mewujudkan kesetaraan gender melalui proses pembelajaran yang memberikan pemahaman kepada peserta didik tentang bagaimana memposisikan peran perempuan dan laki-laki secara seimbang dan adil dalam kehidupan. Dalam konteks pembelajaran PAI, isu gender perlu diinternalisasikan melalui beberapa pendekatan, salah satunya adalah dengan pendekatan pendapat empat mazhab fiqih. Penelitian ini menggunakan pendekatan kualitatif dengan metode studi kepustakaan (library research) untuk mengkaji lebih dalam mengenai konsep gender dalam pendidikan Islam yang berbasis mazhab fiqih. Hasil penelitian menghasilkan desain pembelajaran PAI berbasis gender melalui perbandingan empat mazhab fiqih.